1994
DOI: 10.1117/12.168016
|View full text |Cite
|
Sign up to set email alerts
|

<title>Bone microsurgery with IR lasers: a comparative study of thermal action at different wavelengths</title>

Abstract: The thermal response of cortical bone targets to fiber delivered pulses from fiee running Er:YAG and Ho:Tm:YAG lasers was invesligated expeilinentally and theoretically and compared to histological and morphological findings. The temperatures found at the ablation sites were found to be markedly lower for the strongly absorbed 2.94pin Er:YAG than for the 2.lpm Ho:Tm:YAG pulses. Furthermore, the temporal behavior of the temperature underneath the ablation crater when using 2.lpm pulses suggests that the absorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 0 publications
2
18
0
1
Order By: Relevance
“…With a radiant exposure of H--12 J cm -2, the perforation of the cochlea with a thickness between 120 and 160~m (evaluated after the experiment by morphometry) was possible with 11-17 laser pulses, resulting in an ablation depth of 10 + 2/lm pulse-~ assuming a constant ablation rate for consecutive pulses (27). The diameter of the round hole was typically 350~m.…”
Section: Bone Morphology and Histologymentioning
confidence: 99%
“…With a radiant exposure of H--12 J cm -2, the perforation of the cochlea with a thickness between 120 and 160~m (evaluated after the experiment by morphometry) was possible with 11-17 laser pulses, resulting in an ablation depth of 10 + 2/lm pulse-~ assuming a constant ablation rate for consecutive pulses (27). The diameter of the round hole was typically 350~m.…”
Section: Bone Morphology and Histologymentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22] Recent studies using pulsed TEA and RF-excited CO 2 laser pulses of submillisecond duration indicate that dental hard tissues can be ablated efficiently without generating peripheral damage. [23][24][25][26][27] Ivanenko et al 28 demonstrated that a mechanically Qswitched 10.6 μm CO 2 industrial laser could be used to cut bone rapidly at 300 Hz without thermal damage. The peak absorption of dental hard tissues occurs at 9.3 and 9.6-μm where the incident laser light will be absorbed at a depth of under 1-2 μm (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…29,30 Previous efforts focused on the 9.3 and 9.6-μm TEA lasers that employ a simple high voltage discharge to excite the gas mixture. [23][24][25][26][27]29,30 In contrast, Radio Frequency (RF) excited slab lasers use a radiofrequency source to excite the CO 2 gas and can be operated efficiently with a completely sealed gas mixture. The principal advantages of the RF-slab laser over the TEA laser are small size and sealed gas mixture.Systems with output in the range of 10-30 W are now available at relatively low-cost that do not require water-cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Er:YSGG laser emission is coincident with the narrow (OH) absorption band at λ=2.8 μm while Er:YAG emission overlaps the broad water absorption centered at λ=3 μm. It is the generally accepted hypothesis that the subsurface expansion of water is the primary mechanism responsible for exfoliation or spallation of the enamel mineral at temperatures below the melting point of the tissue (~1200°C) during irradiation near λ=3 μm 7,9,10,12,16,[18][19][20][21][22] . During rapid heating, the inertially confined water can create enormous subsurface pressures that can lead to the explosive removal of the surrounding mineral matrix 11 .…”
Section: Introductionmentioning
confidence: 99%
“…During rapid heating, the inertially confined water can create enormous subsurface pressures that can lead to the explosive removal of the surrounding mineral matrix 11 . Several studies of hard tissue ablation in the λ=3.0 μm region indicate that large particles are ejected with high velocity from the irradiated tissue 7,9,10,20,23 . This observation strongly supports the mechanism of a water-mediated explosive process.…”
Section: Introductionmentioning
confidence: 99%